Las audiencias telemáticas penales como consecuencia del estado de excepción por Covid-19 y la vulneración al principio de inmediación - Karenn Lisbeth, Carvajal Motesdeoca (2021)
Abstract The President of the Republic of Ecuador, through ordinance number 1017, declared state of exception due to public catastrophe throughout the country because of the rise of confirmed coronavirus cases. The mandate established the interruption of the in-person business day for the public and private workers indicating that employees should develop their duties via telework. The Plenary of the Judiciary Council implemented the modality of telematic hearings. The problem is that by turning the exception into a rule, the violation of the procedural principle of immediacy becomes common since the defendant does not have direct contact with the judge and the other procedural subjects. Online hearings have impacted defendants’ rights although online hearings are justified by the Covid-19 pandemic. There is no doubt that online hearings have influenced the administration of justice. This study suggests that telematic hearings violate the principle of immediacy for several reasons such as lack of a regulatory framework that ensures its validity, inadequate means to properly proceed with the hearing, scarce technological platforms to guarantee the simultaneity of audio and video, lack of training of the professionals who intervene in the hearing, and intermittence of the internet connection. The fact that the judge can directly perceive everything that happens at the hearing to form his conviction seriously threatens the procedure as determined in the results of the survey applied to judicial employees. Reviewed by MsC. Adriana Cundar Ph.D. ENGLISH PROFESSOR c.c. 1709268534